2013
DOI: 10.1515/hsz-2013-0219
|View full text |Cite
|
Sign up to set email alerts
|

Molecular triggers of neuroinflammation in mouse models of demyelinating diseases

Abstract: Myelinating cells wrap axons with multi-layered myelin sheaths for rapid impulse propagation. Dysfunctions of oligodendrocytes or Schwann cells are often associated with neuroinflammation, as observed in animal models of leukodystrophies and peripheral neuropathies, respectively. The neuroinflammatory response modulates the pathological changes, including demyelination and axonal injury, but also remyelination and repair. Here we discuss different immune mechanisms as well as factors released or exposed by mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Another Plp1 overexpressing mouse model (homozygous line 72) (Anderson et al, 1998) has been investigated with regard of a possible impact of inflammation on pathogenesis. Showing a quite similar inflammatory phenotype in the optic nerve as seen in the line 66, disturbed axonal transport was spatially associated with local inflammation and perturbed myelin in these mutants (Barrette, Nave, & Edgar, 2013;Edgar et al, 2010). These combined observations reveal that lack of PLP, introduction of Plp1 point mutations, and different degrees of Plp1 overexpression commonly funnel down in pathogenically relevant neuroinflammatory reactions.…”
Section: Pelizaeus-merzbacher Disease a N D Sp A S T I C P A R A P mentioning
confidence: 57%
See 2 more Smart Citations
“…Another Plp1 overexpressing mouse model (homozygous line 72) (Anderson et al, 1998) has been investigated with regard of a possible impact of inflammation on pathogenesis. Showing a quite similar inflammatory phenotype in the optic nerve as seen in the line 66, disturbed axonal transport was spatially associated with local inflammation and perturbed myelin in these mutants (Barrette, Nave, & Edgar, 2013;Edgar et al, 2010). These combined observations reveal that lack of PLP, introduction of Plp1 point mutations, and different degrees of Plp1 overexpression commonly funnel down in pathogenically relevant neuroinflammatory reactions.…”
Section: Pelizaeus-merzbacher Disease a N D Sp A S T I C P A R A P mentioning
confidence: 57%
“…In the corresponding animal models, generated in different laboratories, the inflammatory component appears to be nearly absent (Berger et al, 2014;Moser, 2004), an unfortunate prerequisite for studying the respective, immune-related pathomechanisms. However, future studies are required to elucidate whether the inflammatory reactions in the form of microgliosis and increased numbers of CD81 T-lymphocytes contribute to the demyelinating phenotype (Barrette et al, 2013). As an alternative to the X-ALD mutants, mice with an inactivated peroxisomal biogenesis factor peroxin-5 in oligodendrocytes recapitulate the phenotype of inflammation-associated X-ALD (Kassmann et al, 2007).…”
Section: Leukodys Trophies Unrelated T O Hspmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that inflammation can lead to myelin dysfunction, oligodendrocyte death, and the degeneration of myelinated neurons (Barrette, Nave, & Edgar, ). In addition, astrocyte‐derived proinflammatory cytokines induce hypomyelination in the periventricular white matter of hypoxic neonatal rats (Deng et al, ).…”
Section: Impact Of Immune System Activation On Alcohol‐induced Brain mentioning
confidence: 99%
“…For example, several autoimmune diseases (Guillain-Barré syndrome in the PNS and multiple sclerosis in the CNS) (Kamm and Zettl, 2012), inherited disorders affecting structural genes in myelin (Charcot-Marie-Tooth disease, Dejerine-Sottas syndrome and Pelizaeus-Marzbacher disease) (Kleopa et al ., 2010; Barrette et al ., 2013), metabolic disorders (Canavan, Menke’s, Krabbe’s and Refsum’s disease) (Kumar et al ., 2006), infection, trauma, toxins (including alcohol or drugs), hormonal imbalance and asphyxia are the cause of such dysfunction (Kohlhauser et al ., 2000). Additionally, astrocyte-related diseases like Alexander disease result in severe hypomyelination, mental retardation and death (Ettle et al ., 2016).…”
Section: Dysregulated Myelination and Psychiatric Disordersmentioning
confidence: 99%